Differential Effects of Fatty Acid Saturation and Chain Length on NASH in Juvenile Iberian Pigs. (29th May 2020) - Dillard, Kayla; Coffin, Morgan; Hernandez, Gabriella; Smith, Victoria; Johnson, Catherine; Immoos, Chad; Blank, Jason; Glanz, Hunter; Fanter, Rob; Burrin, Doug; Frano, Michael La; Manjarin, Rodrigo; et al.
Abstract: Objectives: Non-alcoholic fatty liver disease (NAFLD) represents the major cause of pediatric chronic liver pathology in the United States. The objective of this study was to compare the relative effect of inclusion of isocaloric amounts of saturated medium-chain fatty acids (hydrogenated coconut oil), saturated long-chain fatty acids (lard) and unsaturated long-chain fatty acids (olive oil) on endpoints of NAFLD and insulin resistance. Methods: Thirty-eight 15-d-old Iberian pigs were fed 1 of 4 diets containing (g/kg body weight × d) 1) control (CON; n = 8): 0 g fructose, 10.5 g fat, and 187 kcal metabolizable energy (ME), 2) lard (LAR; n = 10): 21.6 g fructose, 17.1 g fat (100% lard) and 299 kcal ME, 3) hydrogenated coconut oil (COCO; n = 10): 21.6 g fructose, 16.9 g fat (42.5% lard and 57.5% coconut oil) and 299 kcal ME, and 4) olive oil (OLV, n = 10): 21.6 g fructose, 17.1 g fat (43.5% lard and 56.5% olive oil) and 299 kcal ME, for 9 consecutive weeks. Body weight was recorded every 3 d. Serum markers of liver injury and dyslipidemia were measured on d 60 at 2 h post feeding, with all other serum measures assessed on d 70. Liver tissue was collected on d 70 for histology, triacylglyceride (TG) quantification, and metabolomics analysis. Results: Tissue histology indicated the presence of steatosis in LAR, COCO and OLV compared with CON ( P ≤ 0.001), with a further increase in in non-alcoholic steatohepatitis (NASH) in OLV and COCO compared with LAR ( P ≤ 0.01). Alanine and aspartate aminotransferases were higher in COCO and OLV ( P ≤ 0.01) than CON. All treatment groups had lower liver concentrations of methyl donor's choline and betaine versus CON, while bile acids were differentially changed ( P ≤ 0.05). COCO had higher levels of TGs with less carbons (Total carbons < 52) than all other groups ( P ≤ 0.05). Several long-chain acylcarnitines involved in fat oxidation were higher in OLV versus all other groups ( P ≤ 0.05). Conclusions: Inclusion of fats enriched in medium-chain saturated and long-chain unsaturated fatty acids in a high-fructose high-fat diet increased liver injury, compared with fats with a long-chain saturated fatty acid profile. Further research is required to investigate the mechanisms causing this difference in physiological response to these dietary fat sources. Funding Sources: ARI, AcornSeekers.